Radical-mediated decomposition and polymerization for rapid humification and pollutant removal of livestock manure - Mengyu Ma; Hengtong Liu; Jianing Gai; Wenhan Liu; Yanqin Wang; Lushan Wang; Defang Ma; Rutao Liu; Qian Li (Bioresource Technology, 2026)

Secondary structure-regulated self-assembly of zein: mechanisms, morphological regulation, and adsorptive removal of pollutants in wastewater - Defang Teng; Weitai Sun; Yiyou Liu; Xiaolu Ma; Bo Yang; Wei Li; Zengge Guo (Journal of Environmental Sciences, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Dose–dependent effect of Bacillus subtilis on aquaculture pond ecosystems - Weiming Liu; Xiaolong Bo; Yanhao Cao; Jianchun Xiao; Run Zhang; Hongli Liu; Defang Chen; Yi Geng; Ping Ouyang; Xiaoli Huang (World Journal of Microbiology and Biotechnology, 2026)

Degradation of p-Nitrophenol (PNP) via photocatalytic ozonation using perylene diimide polymer - Defang Liu; Chao Wang; Zhuo Cheng; Qiyao Zhao; Xuelian Zeng; Chiyu Wen; Jing Zhao; Guoxiang Zhu; Jun Wang; Yongfa Zhu (Chemical Engineering Journal, 2026)

LncRNA AC098613.1 promotes acute myeloid leukemia cell differentiation through CDC5L/ADAP1/NRD1 axis - Qingling Jiang; Xiaoting Wang; Hang Yao; Jince Wang; Peiyu Tang; Mingpeng Liang; Zhaohai Pan; Bohan Li; Chunhua Lin; Qinxuan Wu; Qi Wang; Qiusheng Zheng; et al. (Apoptosis, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

New quality productivity, labor quality and corporate high-quality green development - Ying Liu; Jindong Wang; Defang Ma; Jiahui Ding; Ting Peng (Journal of Environmental Management, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Genetically engineered MSC vesicles encapsulated with dual-gene siRNAs integrated peptide dendrimer nanoplatform for rheumatoid arthritis treatment - Min Nie; Danqing Huang; Defang Meng; Xuanqi Liu; Yuanjin Zhao; Lingyun Sun (Chemical Engineering Journal, 2025)

Preparation and characterization of a novel polyvinyl alcohol/pectin film containing bromocresol green-alizarin mixed indicator label for monitoring mushroom freshness - Yani Liu; Defang Shi; Xiuzhi Fan; Chaomin Yin; Zhicheng Huang; Junlong Meng; Bing Deng; Ying Liu; Cunkun Chen; Hong Gao (Food Packaging and Shelf Life, 2025)

Global landslide mapping using tibetan plateau landslide dataset and improved YOLOX - Defang Liu; Mingjie He; Ben Huang; Qi Dong; Shiqi Liu (Earth Science Informatics, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

Effects of chitosan‑calcium coating on the physiological characteristics and browning of Stropharia rugosoannulata during postharvest storage - Yingqi Zhang; Xi Feng; Defang Shi; Xiaoju Tian; Wen Huang; Ying Liu (Food Research International, 2025)

Evaluation of the antibacterial activity and mechanism of cannabigerol against drug-resistant Streptococcus iniae in vitro - Jianing Wu; Minmin Wang; Tingke He; Xiaonan Li; Bowen Liu; Fen Chen; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Ping Ouyang (Archives of Microbiology, 2025)

Exploring a novel toxicological mechanism: Ammonia-N induces neurotoxicity, oxidative damage in brain tissue, and modulates the expression of central appetite factors to suppress feeding in juvenile Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Qiang Hu; Huimin Sun; Jun Li; Ruitian Xiang; Tonglei Chen; Shuhuang Chen; Youlian Liu; Peng Tang; Ni Tang; Zhiqiong Li; Defang Chen (Aquaculture, 2025)

Effect of cortisol through GR regulated inflammatory cytokine expression and apoptosis of Siberian sturgeon (Acipenser baerii) after LPS treatment - Peng Tang; Hao Zhu; Defang Chen; Yinqiu Chen; Shuhuang Chen; Youlian Liu; Xin Zhang; Xiaoli Huang; Zhiqiong Li; Ping Ouyang; Yi Geng (Aquaculture, 2025)

Development and evaluation of suitable reference genes for qRT-PCR normalization of hybrids derived from Lycium barbarum and Lycium ruthenicum - Yu Liu; Wenjun Shi; Defang Zhang (Molecular Biology Reports, 2024)

Histopathology and transcriptome profiling reveal features of immune responses in gills and intestine induced by Spring viremia of carp virus - Ping Ouyang; Qiunan Li; Shuya Liu; Yankai Li; Shuhan Li; Yongheng Zhou; Peng jia; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2024)

Neglected function of gastrin to reduce feeding in Siberian sturgeon (Acipenser baerii) via cholecystokinin receptor B - Shupeng Zhang; Yongpei Lu; Yanling Liu; Mei Wang; Shaoqi Xu; Ya Li; Hongwei Wu; Qaolin Pei; Lei Yang; Lu Lu; Yixiao Xiong; Youlian Liu; et al. (Fish Physiology and Biochemistry, 2024)

Long-term dietary exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) reduced feeding in common carp (Cyprinus carpio): Via the JAK-STAT signaling pathway - Xin Zhang; Youlian Liu; Huimin Sun; Shuhuang Chen; Peng Tang; Qiang Hu; Mengxuan He; Ni Tang; Zhiqiong Li; Defang Chen (Environmental Pollution, 2024)

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Brain-derived neurotrophic factor (BDNF) activates PI3K-AKT-mTOR signaling via hypothalamic TrkB receptors to reduce feeding in Siberian sturgeon (Acipenser baerii) - Shupeng Zhang; Yongpei Lu; Yingzi Li; Yanling Liu; Qin Yao; Qin Kang; Shuhuang Chen; Youlian Liu; Yixiao Xiong; Defang Chen; Xin Zhang; Ni Tang; et al. (Aquaculture, 2024)

The potential mechanism of concentrated mannan-oligosaccharide promoting goldfish’s (Carassius auratus Linnaeus) resistance to Ichthyophthirius multifiliis invasion - Senyue Liu; Ming Xu; Baipeng Chen; Fulong Li; Yongqiang Deng; Yufan Zhang; Gang Lin; Defang Chen; Yi Geng; Yangping Ou; Xiaoli Huang (Fish & Shellfish Immunology, 2024)

PBPK/PD Modeling of Nifedipine for Precision Medicine in Pregnant Women: Enhancing Clinical Decision-Making for Optimal Drug Therapy - Xinyang Liu; Wei Wang; Jingsi Chen; Dunjin Chen; Yong Tao; Defang Ouyang (Pharmaceutical Research, 2024)

High starch diets attenuate the immune function of Micropterus salmoides immune organs by modulating Keap1/Nrf2 and MAPK signaling pathways - Hongli Liu; Baipeng Chen; Yanhao Cao; Yi Geng; Ping Ouyang; Defang Chen; Liangyu Li; Xiaoli Huang (Fish & Shellfish Immunology, 2023)

First report of a CMTV-like ranavirus in farmed Percocypris pingi in China - Fan Liu; Silu Tian; Yang Feng; Zhenyang Qin; Yi Geng; Yangping Ou; Defang Chen; Xiaoli Huang; Hongrui Guo; Zhicai Zuo; Huidan Deng; Weimin Lai (Aquaculture, 2023)

Salvia miltiorrhiza polysaccharides enhance the antioxidant capacity and immune resistance of hybrid sturgeon (Acipenser baerii♀ × Acipenser schrenckii♂) against Streptococcus iniae infection - Defang Chen; Hao Zhu; Daiyu Chen; Lei Yang; Fei Yang; Qiaolin Pei; Yue He; Xin Zhang; Lianshi Qu; Tianqiang Liu; Yi Geng; Zhiqiong Li (Aquaculture International, 2023)

Physiologically Based Pharmacokinetic Modeling for Multiple Oral Administration Labetalol in Pregnant Women - Yudi Song; Wei Wang; Xinyang Liu; Jingsi Chen; Dunjin Chen; Xiaoyi Wang; Wei Li; Defang Ouyang (Pharmaceutical Research, 2023)

The IL17 signaling pathway: A potential signaling pathway mediating gill hyperplasia and inflammation under ammonia nitrogen stress was identified by multi-omics analysis - Liang Zhong; Sha Liu; FengYuan Zuo; Yi Geng; Ping Ouyang; Defang Chen; Shiyong Yang; Wei Zheng; Yinlin Xiong; Wenlong Cai; Xiaoli Huang (Science of The Total Environment, 2023)

Galanin, a central appetite factor, affects appetite signals in the hypothalamus and promotes feeding in Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Shuhuang Chen; Hongwei Wu; Zhengzhi Tian; Ni Tang; Youlian Liu; Peng Tang; Qiang Hu; Yingzi Li; Qin Kang; Defang Chen; Zhiqiong Li (Aquaculture, 2023)

Cloning and expression of kiss genes and regulation of feeding in Siberian sturgeon (Acipenser baerii) - Shaoqi Xu; Mei Wang; Ya Li; Ni Tang; Xin Zhang; Hu Chen; Shupeng Zhang; Yanling Liu; Jun Wang; Defang Chen; Zhiqiong Li (Fish Physiology and Biochemistry, 2022)

Development of a Highly Water-Soluble Lycopene Cyclodextrin Ternary Formulation by the Integrated Experimental and Modeling Techniques - Yan Ma; Liuting Zhong; Zhuo Peng; Xinyang Liu; Defang Ouyang; Shixia Guan (AAPS PharmSciTech, 2021)

Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon ( Acipenser baerii ) - Ni Tang; Yanlin Liu; Zhengzhi Tian; Shaoqi Xu; Mei Wang; Hu Chen; Bin Wang; Ya Li; Yan Wang; Song Yang; Liulan Zhao; Defang Chen; et al. (Journal of Fish Biology, 2020)
Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

The rice “fruit-weight 2.2-like” gene family member OsFWL4 is involved in the translocation of cadmium from roots to shoots - Wentao Xiong; Peng Wang; Tianze Yan; Baobao Cao; Jun Xu; Defang Liu; Meizhong Luo (Planta, 2018)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Ya-fish (Schizothorax prenanti) spexin: identification, tissue distribution and mRNA expression responses to periprandial and fasting - Hongwei Wu; Fangjun Lin; Hu Chen; Ju Liu; Yundi Gao; Xin Zhang; Jin Hao; Defang Chen; Dengyue Yuan; Tao Wang; Zhiqiong Li (Fish Physiology and Biochemistry, 2016)

Genome-wide analysis of HD-Zip genes in grape (Vitis vinifera) - Haiyang Jiang; Jing Jin; Huan Liu; Qing Dong; Hanwei Yan; Defang Gan; Wei Zhang; Suwen Zhu (Tree Genetics & Genomes, 2015)

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China - Yan Qin; YanHe Li; Feng Liu; KeJun Hou; DeFang Wan; Cheng Zhang (Science China Earth Sciences, 2012)